The SAVI Learning Model Application Assisted by E-Learning-Based Accounting Puzzle Media to Improve Vocational School Students’ Collaboration Skills - Vinky Febriyani Cahya Putri; Sri Sumaryati; Jaryanto Jaryanto (Universitas Sebelas Maret, 2020)
21st Century learning requires a variety of skills that must be mastered by students, one of which is collaboration skills. But the reality shows that the collaboration skills of AKL Class X students in Wikarya Karanganyar Vocational School are only 43,52%, which means that the category is not good. The purpose of this study is to show empirical that the to increase the collaboration skills of students of class X AKL in Wikarya Vocational High School Karanganyar by applying the SAVI (Somatic, Auditory, Visual and Intellectual) learning model are assisted by accounting puzzle based on e-learning. This research is a Classroom Action Research (CAR) carried out in two cycles, with research procedures for each cycle consisting of four stages, namely: (1) planning action, (2) implementation action, (3) observation and interpretation, (4) analysis and reflection. This research subjects was the students of class X AKL 1 SMK Wikarya Karanganyar, amounting to 20 students. Data sources come from teachers and students, who use data collection techniques with observation, interviews, and documentation. The data analysis using critical analysis techniques for qualitative data and comparative descriptive statistical techniques for quantitative data. The results showed with the application of SAVI learning models assisted by Accounting Puzzle based e-learning there was an increase in students' collaboration skills of pre-action, the first cycle, and the second cycle with the. This study sets an indicator of the achievement of collaboration skills of 62,5% or included in good categories. In the pre-research obtained an average percentage of indicators of collaboration skills by 43,52%, included in the bad category. In the first cycle has increased, the average percentage of collaboration skills amounted to 57,72%, included in the category enough. In the second cycle also increased, the average percentage of collaboration skills indicators was 72,85%, included in good categories. Based on this research, SAVI learning model are assisted by accounting puzzle based on e-learning can n increase students’ collaboration skills.